Principles of redox signaling - Forman, Henry Jay (Henry Stewart Talks, 2023)
Principles of redox signaling, Physiological redox signaling versus oxidative stress responses, Signaling by endogenously generated H2O2, NOX complexes and superoxide production, H2O2 as a second messenger, Glutathione (GSH) in peroxide metabolism, Thioredoxin in peroxide metabolism, Glutathionylation, Oxidation of the thiol form, Sulfenyl amides